University Student Engagement Inventory: Validation in the Indian Online Learning Context - Sharif-Nia, Hamid; Maroco, Joao; She, Long *; Narula, Sumit; Ma, Lan *; Kaveh, Omolhoda; Rahmatpour, Pardis; Ghahrani, Nassim (Taylor and Francis Group, 2024)
Objective This study aims to evaluate sources of validity and reliability of the University Student Engagement Inventory among Indian Students.